Factors of increase of efficiency of fixed capital - Kerimbekova Kabdeshova, N. A. N. A. (Journal of Economic Research & Business Administration, 2016)
The main purpose of the article factors improving the efficiency of fixed capital in the implementation of industrial and innovation policy in the country. The article discusses the development of domestic science-intensive industries at the present time, the development and adoption of new information technologies, focused on obtaining competitive products, ensuring the interests of national economic security through the preservation and development capacity of industry and scientific technology of the Republic, as well as the regular improvement of the technical condition of fixed assets in enterprises, the organization policy of constant renewal of fixed assets in Kazakhstan. At the present time, the actual problem is the renewal of fixed capital. There is a need for innovative and investment resources to accelerate the replacement in time, technical equipment, modernization, reconstruction. The surge in new technology enterprises, particularly insufficient investment for the acquisition of products of engineering industry. In recent years the rate of investment in the manufacturing sector are underestimated due to the low technical base of the enterprise and due to the lack of attractiveness of the investment. In the mining industry the majorit of investments directed to the oil and gas sector.